Removal of methyl orange (MO) using carbon quantum dots (CQDs) derived from watermelon rinds - U. R., Ramzilah; Azrina, Abd Aziz (Penerbit UMP, 2019)
In this study, carbon quantum dots (CQDs) was prepared via a facile hydrothermal method. The objective for this study is to assess the performance of CQDs in photocatalytic degradation activity of methyl orange (MO) under artificial visible light source. For that reason, the prepared photocatalyst undergo further characterization by scanning electron microscope (SEM), energy dispersive X-ray spectroscope (EDX) and UV- Vis spectrophotometer (UV-VIS) to verify the morphology structure of the photocatalyst, elemental composition as well as the absorbance intensity, respectively. The results indicates that the prepared photocatalyst possess irregular porous shape with nanometre (nm) dimensions that can escalate the surface area for photocatalytic degradation activity. The elements of the photocatalyst mainly consist of carbon and oxygen as the major constituents in which necessary for photocatalytic activity with intense peak of absorbance intensity. The prepared CQDs also shows an excellent photocatalytic performance over the MO with degradation rate of 68.9% within 120 minutes.